Do CSR Activities Influence Cash Holding Policy in European Countries? - Mhadhbi, Feker (STIE Malangkucecwara, 2024)
The purpose of this article is to check whether socially responsible activities influence the cash holding policy in European companies. Using a sample of 1,352 European companies during 2006-2015, we find that companies with good social performance hold less cash than companies with lower social performance. We also found that in European countries that guarantee good investor protection, CRS companies accumulate less cash. Taking into account the legal origin of the countries, we have noticed that socially successful companies operating in common law are less likely to hold high cash levels. These resuslts suggest that in the presence of good environment that ensures good investor protection, the negative effect of CSR activities on the level of cash holding is accentuated.